Analysis of bicycle sharing economy - KIM, Hwajin (KDI School, 2017)
Countries are in transition to a low-carbon and climate-resilient economy to achieve sustainable development. One of the important ways into the sustainable growth path is carbon reduction, which is especially true in Korea with high proportion of road vehicle. Therefore, this paper investigates bicycle sharing economy as an emerging and alternative mode of transportation service and provides potential managerial and policy implications. Since bicycle sharing economy is still at an early stage of introduction as a transportation mode, the government is promoting public bicycle sharing to encourage bike riding as a substitute for private car. This study analyzed the current status of bicycle sharing programs through survey which was distributed randomly to users and non-users across the country. Using factor analysis, the overall attitudes such as satisfaction and loyalty for the existing users, and intention to use and expected satisfaction for the potential users were examined in relation with utility factors. The findings of the study could be applicable to the future direction of sharing economy as a means to follow sustainable development of society.
Thesis(Master) --KDI School:Master of Development Policy,2017